INCREASING STUDENTS LISTENING SKILLS THROUGH SONG AND AUTHENTIC VIDEO - Ni Luh Komang Galih Srirejeki; Putu Sri Darmayanti (Yavana Bhasha : Journal of English Language Education, 2019)
The research aimed to investigate whether the usage of songs and authenticvideos were able to increase students listening ability. The purpose was to find outwhether the students who taught by songs and authentic videos achieved betterimprovement to compare to those who did not. Most of the researchers usedexperimental methods. The questionnaire and data collection were used to analyzehow this activity affected. The students who were taught using song and authenticvideo got better outcomes rather than those who were taught using the usual. Thequestionnaire responses showed that the students preferred the authentic listeningmaterials. Those were more interesting and more related to their real-life context sothat it could motivate them to give more attention to the listening class and this alsoassisted them to improve their listening ability.